Frequency Survey of Bacterial Contamination of Mobile Cell Phones in General Population in Tehran, Iran - Matini, Esfandiar; Shayeghi, Farzad; Nematian, Javad; Shayeghi, Homeyra; Lazemi, Vahideh; Rezarian Ghahroud, Reihaneh; Shahbazi, Fatemeh; Madari Mohades, Seyed Amir Mahdi; Zarghami, Amin; Ghasemzadeh Kolagar, Hossein; Rahmani, Helia; Abasi Feshki, Hanieh; et al. (Galen Medical Journal, 2023)
Background: Mobile smart phones have become increasingly integrated into the daily lives of individuals in society. Recent studies indicated the considerable role of these devices as reservoirs for various micro-organisms. The objective of this study was to assess the prevÂalence of microbiological contamination of mobile phones in general population. Materials and Methods: This cross-sectional study included a large sample of mobile phones of genÂeral population Tehran in 2015. Samples for culture were collected from mobile phones and transported for microbiological identification based on standard laboratory methods. Results: Bacteriological analysis revealed that in total of 5220 sample retrieved, 5180 (98.9%) mobile phone devices were contaminated with bacteria. The most common microorganisms that were isolated include: Staphylococcus epidermidis (63.9), Escherichia coli (12.3%) and StaphyloÂcoccus aureus (11.4%). Conclusion: The prevalence of mobile phone contamination is high in general population in Tehran. Although most of the isolated organisms seemed to be non-pathoÂgenic, their colonization may endanger certain populations particularly in health care settings. [GMJ.2016;5(2):70-74]